2015
DOI: 10.5812/ircmj.19960
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing Activity of a Traditionally Used Poly Herbal Product in a Burn Wound Model in Rats

Abstract: Background:Burns are known as one of the most common and destructive forms of injury with a vast spectrum of consequences. Despite the discovery of various antibacterial and antiseptic agents, burn wound healing still has remained a challenge to modern medicine. Plants, with a valuable traditional support, have been considered as potential agents for prevention and treatment of disorders in recent years. However, modern scientific methods should be applied to validate the claims about the therapeutic effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…Research on topical administration of natural ingredients that have antioxidant activity proved to improve the process of wound healing and prevent tissue damage due to oxidative stress [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on topical administration of natural ingredients that have antioxidant activity proved to improve the process of wound healing and prevent tissue damage due to oxidative stress [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…After wound occurred, the healing phase that involved are inflammation, proliferation and remodeling [18].…”
Section: Introductionmentioning
confidence: 99%
“…35 Modern research findings confirm the traditional knowledge. 161,183,[248][249][250][251][252][253][254][255][256][257][258] But carefully reviewing this data reveals an interesting and not always consistent results. For example, it is reported that chloroform and n-hexane extracts of M. parviflora are irritant.…”
Section: Figure 6 Structures Of Malvalic and Sterculic Acids And Carmentioning
confidence: 99%
“…Total phenolic content, antimicrobial and antioxidant activities PHC were determined. 256 A cream (1%) was prepared from aqueous extract of flowers used to treat surgical blade induced wounds in mice. After 10 days healing was almost complete.…”
Section: Skin Disorders and Wound Healingmentioning
confidence: 99%
“…Medicinal plants are important sources of medicines and presently constitute about 25% of pharmaceutical prescriptions [1]. According to the World Health Organization, the traditional medicine system continues to play an important role in healthcare system since over 80% of the population in the third world countries relies on traditional medicine [2].…”
Section: Introductionmentioning
confidence: 99%